Elementos para a apreensão da dimensão regional do urbano-metropolitano na atualidade - Olga Lúcia Castreghini de Freitas-Firkowski (Confins)
The regional dimension is highlighted in contemporary propositions that aim to understand the urban-metropolitan reality. This is because urbanization has produced new spatial expressions in the last decades, part of them, apprehended through a diversity of concepts in which the region stands out, among others, can be pointed: city-region, megaregion and urban- and others where the regional dimension - although not explicitly - is present, such as the urban corridors and megalopolis. Such concepts are the result of the increasing complexity of the metropolis and show the immense proportions that such spatialities have reached. From the theoretical point of view, it is fundamental to recognize the regional dimension of these new urban-metropolitan spatialities, and from the applied point of view, it is necessary to operate new indicators and variables that result in adequate readings of this reality and contribute to reveal the dynamics of our time. Thus, the present article aims to recover some theoretical propositions and their applied content, besides presenting two recent works, respectively, “arranjos populacionais” (IBGE, 2015) and the Brazilian urbanization scales (Moura; Oliveira; Pêgo, 2018), which offer new possibilities to increase the spatial analysis, surpassing the classic divisions of territory and inserting a variety of new elements that must be observed.